1984
DOI: 10.1017/s004317450005966x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Velvetleaf (Abutilon theophrasti) Germination and Growth by Benzyl Isothiocyanate, a Natural Toxicant

Abstract: Benzyl isothiocyanate (BITC) was extracted from mature papaya (Carica papayaL.) seeds and applied to imbibed velvetleaf (Abutilon theophrastiMedic. ♯3ABUTH) seeds. Complete inhibition of germination occurred at a concentration of 6 × 10-4M BITC, and only 28% (compared to controls) of the seeds germinated after 4 days exposure to the 4 × 10-4M treatment. Corn (Zea maysL. ‘DeKalb XL-66′) was unaffected even at higher concentrations; however, 72% of imbibed soybeans [Glycine max(L.) Merr. ‘Tiger’] germinated in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 10 publications
2
40
2
3
Order By: Relevance
“…Mason-Sedun et al (1986) and Oleszek (1987) have reported residues and macerates of tissues of B. juncea and B. nigra, which contained allyl isothiocyanate, to be inhibitory to wheat, barnyard grass and lettuce. Benzyl isothiocyanate, previously reported to be an inhibitor of velvet leaf ( Abutilon theophrasti) by Wolf et al (1984) was only moderately active in the present experiments. The only isothiocyanate without activity was the butyl derivative, whose occurrence in nature is limited.…”
Section: Compoundcontrasting
confidence: 79%
See 1 more Smart Citation
“…Mason-Sedun et al (1986) and Oleszek (1987) have reported residues and macerates of tissues of B. juncea and B. nigra, which contained allyl isothiocyanate, to be inhibitory to wheat, barnyard grass and lettuce. Benzyl isothiocyanate, previously reported to be an inhibitor of velvet leaf ( Abutilon theophrasti) by Wolf et al (1984) was only moderately active in the present experiments. The only isothiocyanate without activity was the butyl derivative, whose occurrence in nature is limited.…”
Section: Compoundcontrasting
confidence: 79%
“…1), the involatile precursor of allyl isothiocyanate, and its products have been suggested to be allelopathic (Evenari, 1949) and Kutacek (1964) claimed similar activity for the indole glucosinolate, glucobrassicin (Ig). Benzyl isothiocyanate, from glucotropaeolin (Ie), has been similarly described by Wolf et al (1984).…”
Section: Introductionmentioning
confidence: 96%
“…The susceptibility of plant species to an allelochemical under laboratory conditions principally depends on the physiological and biochemical properties of each plant. It was reported that the different sensitivity of a receiver plant to an allelochemical and to the phytotoxic extracts of a donor plant depended on the plant organs (Hasegawa et al 1992c;Suzuki et al 2001;Iqbal et al 2002) and growth stages (Wolf et al 1984;Horie et al 1989;Hasegawa et al 1992c;Li et al 1993;Kobayashi & Ito 1998). Jose & Gillespie (1998b) found that juglone inhibited soybean growth more than corn growth.…”
Section: Response Of Receiver Plant To Allelochemicalmentioning
confidence: 99%
“…ITCs show toxic effects against plants. The growth of velvetleaf seedlings was inhibited by benzyl ITC (Wolf et al, 1984) and sulforaphene (Brinker and Spencer, 1993). ITCs showed allelopathic effects on wheat (Bialy et al, 1990;Vaughn and Berhow, 1999).…”
Section: Introductionmentioning
confidence: 99%